Comparison of CT-measured angles of pelvic limbs without patellar luxation of six canine breeds - Brühschwein, Andreas; Burg-Personnaz, Juliette; Zöllner, Martin; Reese, Sven; Meyer-Lindenberg, Andrea (Frontiers in Veterinary Science, 2023)
Dogs with medial patellar luxation can be affected by pelvic limb deformities whose corrective osteotomies and associated biomechanical rebalancing might provide higher success rates than standard surgical procedures limited to the stifle joint. In bilaterally affected canine patients, comparison with the contralateral normal limb is impossible. Reference values are useful for orthopedic decision-making. Inconsistency of published reference values might depend on methodology or canine breed. We hypothesized that canine pelvic limb alignment is breedspecific. "CT scans of 42 pelvic limbs of dog breeds predisposed for medial patellar luxation, with an orthotopic patellar position and stability were studied. Several angleswere measured with an open-source 3D Slicer plugin using vector calculations. The breeds were compared with a general linear model with a Bonferonni adjustment using SPSS. Chihuahuas, Pomeranians, Jack Russel Terriers, Pugs, French Bulldogs, Maltese were examined. In the order of the listed breeds, the angles were as follows: 28.